Regional analysis of planting date and cultivar maturity recommendations that improve soybean oil yield and meal protein concentration - Salmerón, Montserrat; Bourland, Fred M.; Buehring, Normie W.; Earnest, Larry; Fritschi, Felix B.; Gbur, Edward E.; Golden, Bobby R.; Hathcoat, Daniel; Lofton, Josh; McClure, Angela Thompson; Miller, Travis D.; Neely, Clark; et al. (Frontiers in Plant Science, 2022)
Planting date and cultivar maturity are major management factors affecting soybean [Glycine max (L.) Merr.] productivity, but their effect on seed protein and oil concentration, and in particular meal protein concentration, is less understood. We quantified changes in seed oil and protein concentrations, estimated meal protein concentration, and total oil and protein yield in response to planting date and cultivar maturity group (MG) ranging from 3 to 6 and across locations comprising a 8.3º range in latitude in the U.S. Midsouth. Our results show that delayed planting date and later cultivar maturity reduced oil concentration, and this was partially associated with a decrease in temperature during the seed fill phase. Thus, optimum cultivar MG recommendations to maximize total oil yield (in kg ha-1) for planting dates in May and June required relatively earlier cultivar MGs than those recommended to maximize seed yield. For planting dates in April, short-season MG 3 cultivars did not increase oil yield compared to full-season MG 4 or 5 cultivars due to a quadratic yield response to planting date at most locations. Planting date and cultivar maturity effects on seed protein concentration were not always consistent with the effects on meal protein concentration after oil extraction. Meal protein concentration decreased when the start of seed fill occurred after August 15, but short-season cultivar MGs reduced the risk of low meal protein concentration. This study provides cultivar MG and sowing date strategies for maximizing oil yield, as well as for increasing meal protein concentration without sacrificing seed yield.